Books Books
If any number of quantities are proportional, any antecedent is to its consequent as the sum of all the antecedents is to the sum of all the consequents. Let a : b = c : d = e :f Now ab = ab (1) and by Theorem I.
An Elementary Geometry - Page 30
by William Frothingham Bradbury - 1872 - 110 pages

## Algebra for Secondary Schools

Webster Wells - Algebra - 1906 - 484 pages
...О (л Яi— ПГ~ т TI "VCl Vс In like manner, -1— = — — 344. In a series of equal ratios, any antecedent is to its consequent as the sum of...the sum of all the consequents. Let a : b = c: d = e :/. Then by § 331, ad — be, and af= be. Also, a6 = ba. Adding, а(b + d +/) = b(a + с + e). Whence,...

## Plane and Solid Geometry

Isaac Newton Failor - Geometry - 1906 - 440 pages
...13 = x — y : 3, find the ratio of x to y. PROPOSITION IX. THEOREM 336 In a continued proportion, any antecedent is to its consequent as the sum of...antecedents is to the sum of all the consequents. PROOF ab = ba, Iden. ad = be, § 328 and of = be. . § 328 Adding, ab + ad + af= ba + be + be ; Ax....

## Plane and Solid Geometry

Isaac Newton Failor - Geometry - 1906 - 431 pages
...Ifx+y:l3 = x — y:3, find the ratio of x to y. PROPOSITION IX. THEOREM 336 In a continued proportion, any antecedent is to its consequent as the sum of...antecedents is to the sum of all the consequents. PROOF ab = ba, I den. ad = be, § 328 and af = be. § 328 Adding, ab + ad -f <tf= ba + &c + be ; Ax....

## Algebra for Secondary Schools

Webster Wells - Algebra - 1906 - 550 pages
...-ï— = -^— • л/о л/d 344. //ia series of equal ratios, any antecedent is to its consequent an the sum of all the antecedents is to the sum of all the consequents. Let a:b = c:d = e:f. Then by § 331, ad = be, and of= be. Also, ab = ba. Adding, a(b + d +/) = b(a + с...

## Plane Geometry

Edward Rutledge Robbins - Geometry, Plane - 1906 - 268 pages
...a : b = c : r. ) Proof : am = 6c.and ar = be (?) (290). 301. THEOREM. In a series of equal ratios, the sum of all the antecedents is to the sum of all the consequents as any antecedent is to its consequent. Proof: Set each given ratio = m; thus, acea = m; - = m; - =...

## Plane and Solid Geometry

Edward Rutledge Robbins - Geometry - 1907 - 428 pages
...a : b = c : r. \ Proof : am = be and ar = bc (?) (290). 301. THEOREM. In a series of equal ratios, the sum of all the antecedents is to the sum of all the consequents as any antecedent is to its consequent. „. acea Glven: I-2-/-T To Prove: f±£±i+|= f = 1 , etc....

## A First Course in Algebra

Webster Wells - Algebra - 1908 - 262 pages
...proportion. Let the proportions be ?=v and - = ?• 6 a / ft frl. 149. In a series of equal ratios, any antecedent is to its consequent as the sum of...antecedents is to the sum of all the consequents. Let, a:b = c:d = e:f. Then, - ---/ b b+d+f EXERCISE 59 The following problems lead both to integral and...

## A First Course in Algebra ; A Second Course in Algebra

Webster Wells - Algebra - 1908 - 456 pages
...then, — — — . bd b" d" In like manner, — = ^- • П,, ",~i 152. In a series of equal ratios, any antecedent is to its consequent as the sum of...antecedents is to the sum of all the consequents. e). :b + d+f. (§141) In like manner, the theorem may be proved for any number of equal ratios. 153....